Towards Sustainable and Responsible Investment : A Review and Inventory of the Social Investment Industry’s Activities and Potential in Emerging Markets - International Finance Corporation (International Finance Corporation, Washington, D.C., 2017)
To support the growth of sustainable capital flows, IFC’s advisory services seek to influence, support, and enable capital market stakeholders to better integrate environmental, social, and governance (ESG) factors into capital allocation and portfolio management processes, using IFC’s own investment practices as a model. IFC is playing its part to support the growth of the market by funding the development of enhanced stock market indices, financial instruments, and through targeted market research. In 2003, this report provided the first comprehensive overview of socially responsible investing (SRI) in emerging markets. Its findings showed that the social investment industry, having already achieved striking, ongoing growth in developed countries, could ultimately play an expanded role in emerging markets as well. This summary version of the report can be downloaded in full from IFC’s website, highlights the major findings of the report. Its findings allow us to gauge how far the sustainable investing community has come since the turn of the century when ESG issues were breaking into the mainstream investment field.